Flow injection system design for the determination of brown bismarck dye: Desain sistem injeksi aliran untuk penentuan pewarna bismarck coklat - Saif Haider Madlol Mohammed; Noor Razaq Abbas Raheem; Noor Al-Huda Ali Kazem Mohammed (Academia Open, 2024)
This study presents a low-cost flow injection system for estimating Bismarck brown dye, addressing the need for economical and efficient dye concentration measurement methods. The system's design and optimization process are detailed, focusing on parameters like carrier solution speed, dye model size, frequency, and dilution coefficient. Results show optimal conditions for accurate estimations, with the system outperforming traditional color methods in terms of sensitivity and measurement range. This novel approach offers a practical solution for various analytical applications requiring precise dye concentration assessments, with implications for cost-effective chemical analysis in diverse fields. Highlight: Low-cost flow system for Bismarck brown dye. Optimized for accuracy in dye concentration measurement. Practical and efficient for various analytical applications. Keyword: flow injection system, Bismarck brown dye, low-cost, optimization, dye concentration measurement